Dampak Pencemaran Air terhadap Kesehatan Lingkungan dalam Perspektif Hukum Lingkungan (Studi Kasus Sungai Code di Kelurahan Wirogunan Kecamatan Mergangsan dan Kelurahan Prawirodirjan Kecamatan Gondomanan Yogyakarta) - Dinarjati Eka Puspitasari (Fakultas Hukum Universitas Gadjah Mada, 2009)
This research is aimed to know the contribution government and societies in Yogyakarta for maintaining the water pollution on Code River. Code River is a river in Yogyakarta which has crowded area on its river flow region. The research location is in Code’s river flow region, especially in Kelurahan Prawirodirjan Kecamatan Gondomanan dan Kelurahan Wirogunan Kecamatan Mergangsan Yogyakarta.Data in this research were obtained through field research and library research. The field research was carried out by using interview guidance and sample waste data testing from Balai Besar Teknik Lingkungan (BBTKL) Yogyakarta, whereas the library research was done by documentary study by collecting and analyzing selected laws and regulation which were relevant to the research.The result showed that the environmental data to maintain environment health and social condition in the field research has not been served. Beside that, the result of laboratory testing BBTKL showed that water condition on field research has contained pollutant. However, the government and societies just give less contribution to decrease the effect of water pollution on Code River. In this case, the contribution of laws and regulation has been needed to decrease the water pollution.